2005
DOI: 10.1158/0008-5472.can-04-2119
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Expression of the Translation Inhibitor Programmed Cell Death 4 Suppresses Tumorigenesis

Abstract: Programmed cell death 4 (Pdcd4) is a novel repressor of in vitro transformation. Pdcd4 directly inhibits the helicase activity of eukaryotic translation initiation factor 4A, a component of the translation initiation complex. To ascertain whether Pdcd4 suppresses tumor development in vivo, we have generated transgenic mice that overexpress Pdcd4 in the epidermis (K14-Pdcd4). K14-regulated Pdcd4 expression caused a neonatal short-hair phenotype due to early catagen entry compared with matched wild-type siblings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
207
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(217 citation statements)
references
References 46 publications
9
207
0
1
Order By: Relevance
“…Because of its ability to suppress neoplastic transformation both in vitro (Yang et al, 2003b) and in vivo (Jansen et al, 2005), PDCD4 represents a critical target of miR-21 in oncogenesis. The downregulation of PDCD4 represents a major determinant of the effect of miR-21 on invasion and metastasis in colorectal and breast cancer, in which PDCD4 expression exhibits an Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its ability to suppress neoplastic transformation both in vitro (Yang et al, 2003b) and in vivo (Jansen et al, 2005), PDCD4 represents a critical target of miR-21 in oncogenesis. The downregulation of PDCD4 represents a major determinant of the effect of miR-21 on invasion and metastasis in colorectal and breast cancer, in which PDCD4 expression exhibits an Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…progression (Jansen et al, 2005), invasion and matrix metalloproteinase activation (Yang et al, 2006) and tumor growth (Stalberg et al, 2001). It is also identified as a correlate of induced apoptosis (Shibahara et al, 1995;Zhang and DuBois, 2001) and cellular senescence (Kang et al, 2002).…”
Section: Pdcd4 Regulates Invasion and U-par Expression Jh Leupold Et Almentioning
confidence: 99%
“…Pdcd4 has been described recently as a new tumor suppressor gene, its overexpression being sufficient to inhibit 12-O-Tetradecanoylphorbol 13-acetate 4b,9a, 12b,13a,20-Pentahydroxytiglia-1,6-dien-3-one 12-tetradecanoate 13-acetate (TPA)-induced neoplastic transformation (Cmarik et al, 1999;Yang et al, 2001a), as well as tumor promotion and progression to carcinomas in a transgenic mouse model (Jansen et al, 2005). It was identified in the JB6 mouse epidermal clonal genetic variant cell system as a 64 kDa protein, being preferentially expressed in tumor-promoter-resistant cells and suppressed in promotion-sensitive cells undergoing neoplastic transformation (Cmarik et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] demonstrated that inhibition of COX-2 by the selective inhibitor NS398 increased the mRNA expression of Programmed Cell Death 4 (PDCD4) in colon cancer cells. PDCD4 suppresses the in vitro transformation of mouse keratinocytes induced by 12-Otetradecanoylphorbol-13-acetate (TPA) [9,10] and the promotion and progression of skin carcinogenesis in response to 7,12-dimethylbenz(a)anthracene/TPA in animal models [11]. PDCD4 interacts with translation initiation factors eIF4A and eIF4G and inhibits AP-1 transactivation [9,12].…”
Section: Introductionmentioning
confidence: 99%